A REVIEW ON EMOTIONAL INTELLIGENCE PERCEPTION AMONG EDUCATORS IN POLYTECHNIC - Muniamal (International Journal of Advanced Science and Technology, 2020)
The understanding of Emotional Intelligence is vital in upgrading the quality of education professional development. It is a quality that enables us to confront our emotions, identify others emotions and build good social relationship with others. Educators are role models for students to learn emotionally intelligent behavior and the awareness of emotional intelligence among educators would enable them to enhance personal and professional competence. This study is an attempt to evaluate the insight of emotional intelligence among educators in a Polytechnic. A qualitative approach, with open ended questions and a focus group method was applied. Research conducted implied that there is a need to coach educators on emotionalintelligenceinordertoproducestudentswhoareabletoperformuniversally in future.